2011
DOI: 10.5539/jas.v3n3p93
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of Moist Sludge Piling from Community Wastewater Treatment through the Royal LERD Technology for Growing Rice

Abstract: Using moist sewage sludge as a new source for growing rice is an alternative community wastewater treatment with agricultural benefit and ease management (saves time and space). The experimental study was conducted to investigate the potential of using the moist sludge from community wastewater treatment in growing rice (Oryza sativa L.:Chinat1 rice cultivar). In this experiment, the sludge was divided into 21 treatments, which could be categorized by the level of piling depth and the sun drying time. The slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Supakata et al (2011) showed that using moist sewage sludge as a new source for growing rice was an alternative community wastewater treatment with agricultural benefit and ease management (saved time and space). The finding presented moist sewage sludge piled at the depth of 30 cm could be used to grow rice (Oryza sativa) with sufficient nitrogen.…”
Section: Royal Lerd Project Benefitsmentioning
confidence: 99%
“…Supakata et al (2011) showed that using moist sewage sludge as a new source for growing rice was an alternative community wastewater treatment with agricultural benefit and ease management (saved time and space). The finding presented moist sewage sludge piled at the depth of 30 cm could be used to grow rice (Oryza sativa) with sufficient nitrogen.…”
Section: Royal Lerd Project Benefitsmentioning
confidence: 99%